Successful resection of a huge brainstem enterogenous cyst: case report and literature review - Huang, Boyuan; Miao, Yanming; Jia, Weifeng; Wang, Mengyang; Ren, Cong; Zeng, Wei; Shui, Liangning; Zong, Miao (Frontiers in Oncology, 2024)
Enterogenous cysts (ECs) are rare, benign, congenital ectopic endodermal cysts that only occasionally involve the central nervous system. We presented the diagnosis and treatment of an exceedingly rare case of EC located in the brainstem, which has previously been reported only seven times in pediatric patients. The patient underwent complete surgical resection and experienced no recurrence during the 6-month follow-up. Histopathological examination showed a characteristic cyst wall lined by a monolayer, pseudocompound cubic or columnar epithelium. Preoperative diagnosis of brainstem EC is still challenging. Surgical resection is an effective treatment, and radiotherapy and chemotherapy have not shown reliable therapeutic efficiency.